Analisis Ekuitas Merek Online, Pengalaman Merek, Sikap Merek, dan Keterikatan Merek: Pendekatan Structural Equation Modeling pada Bisnis Ritel - Xiaoyan, Yuan; Asakdiyah, Salamatun; Setiawan, Zunan (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study examines the role of brand experience on brand attitude and brand attachment within the context of online retail. The research utilizes purposive sampling, involving 215 consumers who use applications and engage in online purchases in ZhongShan, Guangdong Province, China. Variance-based Structural Equation Modeling (SEM), also known as SEM-PLS (Partial Least Square Structural Equation Modeling), was employed to test the research hypotheses. The results reveal that brand experience, consisting of affective, sensory, intellectual, and behavioral dimensions, is the second most influential factor in affecting brand attitude and brand attachment. A significant positive relationship between brand experience, brand attitude, and brand attachment was found. These findings highlight that one of the primary goals of marketing is to create a strong bond between consumers and brands, with positive relationships between brand attitude, brand attachment, and practical implications for managerial practices. Additionally, all proposed hypotheses were validated, and the positive relationships between online brand equity, brand experience, and brand attitude underscore the importance of these factors in shaping brand attachment. Consumers tend to have lower brand attachment in online and app-based environments, which may be influenced by the virtual nature of the experience. This study provides valuable insights into the influence of online brand equity, brand experience, and brand attitude in a multichannel context.